PENDEKATAN POLITIS DALAM STUDI ISLAM - Ahmad Musonnif Alfi; Moh. Wildan Romadhoni (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2022)
This article reveals that politics is one of the fields of study that attracts people's attention. Politics has become a serious discussion of ancient Greek philosophers, such as Plato and Aristotle. Politics is a human endeavor to create a good social order. Therefore, politics affects people's lives. An orderly, safe, peaceful, prosperous, physical and spiritual society cannot be separated from the applied political system. The political approach means that it is an effort to understand religion by instilling religious values in social institutions so that motivation or desire arises to achieve happiness and prosperity and peace in society. The relationship between politics and religion cannot be separated. Politics is the result of religious thought in order to create a harmonious and peaceful life in the life of the nation and state. Keywords: Approach, politics, in Islam